Results-Based Financing in Education : Financing Results to Strengthen Systems - World Bank Group (World Bank, Washington, DC, 2017)
Result-based financing (RBF) captures the essence of how the World Bank Group (WBG) is implementing its education strategy, Learning for All. The strategy emphasizes learning (rather than just schooling), since that is what leads to economic growth, development, and poverty reduction. Second, the strategy calls for investing For all so as to ensure the equity dimension behind the Sustainable Development Goals (SDGs) and the Bank’s Twin Goals of reducing poverty and boosting shared prosperity. These goals can be achieved through strengthening education systems. This paper largely focuses on how finance, and RBF specifically, can be used as a lever to pull education systems into coherence. RBF encompasses all of the four transformations called for: performance, innovation, inclusion, and finance. Specifically, putting results first (performance), and embracing results-based approaches to finance (finance) is at the heart of the WBG approach. The approach also offers a new way of approaching problems (innovation), and incentivizing results allows for differentiating levels of rewards, in order to favor traditionally disadvantaged groups, such as rural girls or children living with disabilities (inclusion).